PELAYANAN PERIZINAN TERPADU DI KOTA PALU PROPINSI SULAWESI TENGAH - Nurhannis Nurhannis (Indonesian Journal of Dialectics, 2011)
The research has a strating point a problem at the integrated licensing service Board that gives licensing service that is not suitable with the hope of licensing applicants public. It happens due to perception gap between licensing aplicant public and Palu Government  about licensing urgency, the existence of integrated licensing service. Society as target group and government as the doer have different  view and understanding..The research focuses on licensing service given by government in the integrated licensing service board. The research design uses a desciptive method with a qualitative approach and a case study strategy. The data collection uses observation, interview and kiterature study. The research selut shows that licensing service given by the government is not sulitble with the hope licensing applicant public. The research finds that the more the kinds of licensing integrated into one instance, the bigger the problems will result.